2013
DOI: 10.1159/000354538
|View full text |Cite
|
Sign up to set email alerts
|

Successful Aging in Canada: Prevalence and Predictors from a Population-Based Sample of Older Adults

Abstract: Background: Little research has been conducted to thoroughly explore the prevalence and predicators of successful aging (SA) from a national point of view. Objectives: The objectives of this study were (1) to estimate the prevalence of SA as defined by Rowe and Kahn using a large population-based dataset and (2) to determine the roles of sociodemographic, psychological, and lifestyle factors in SA among Canadian seniors. Methods: Data was from the Canadian Community Health Survey: Healthy Aging (CCHS-HA) (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
44
3
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 24 publications
8
44
3
2
Order By: Relevance
“…The literature is quite inconsistent regarding this evidence. While some studies have shown benefits of moderate alcohol consumption compared with abstaining for healthy aging, others have shown no association or contradictory results …”
Section: Discussionmentioning
confidence: 99%
“…The literature is quite inconsistent regarding this evidence. While some studies have shown benefits of moderate alcohol consumption compared with abstaining for healthy aging, others have shown no association or contradictory results …”
Section: Discussionmentioning
confidence: 99%
“…This finding was similar to those of prior studies investigating the association between marital status and SA in western countries, such as Canada and USA. (Meng & D'Arcy ; Pruchno et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that those who perceived their health as ‘good’ tended to have significantly higher SA scores. Although, to older adults, having objectively good health is important, their subjective health status serves as an important indicator of their overall health (Meng & D'Arcy ; Vaillant & Wolff ). This finding is similar to that of previous studies, in that better subjective health has been reported to be an important factor influencing older adults’ QoL (Kato et al.…”
Section: Discussionmentioning
confidence: 99%
“…Dok su hrvatska istraživanja uspješnog starenja zasada vrlo rijetka, u brojnim su istraživanjima na stranim uzorcima ispitani mnogi potencijalni prediktori, determinante i korelati uspješnog starenja. Među njima, vjerojatno je najbolje potvrđena povezanost uspješnog starenja s dobrim zdravstvenim i funkcionalnim statusom (Depp i Jeste, 2006;Li i sur., 2014;Meng i D'Arcy, 2014;Ng i sur., 2009;Strawbridge i sur., 1996;Vahia i sur., 2012). Sve je više i empirijskih dokaza koji govore u prilog povezanosti uspješnog starenja s različitim psihosocijalnim i varijablama dobrobiti, kao što su zadovoljstvo životom (Meng i D'Arcy, 2014), optimizam (Cosco i sur., 2015;Vahia i sur., 2012), doživljaj smisla života (Windsor i sur., 2015), socijalni odnosi i socijalna podrška (Cosco i sur., 2015;Jeste i sur., 2010;Li i sur., 2014;Ng i sur., 2009;Parslow i sur., 2011;Pruchno i sur., 2010;Strawbridge i sur., 1996) i druge.…”
unclassified